2013
DOI: 10.1002/jsfa.6273
|View full text |Cite
|
Sign up to set email alerts
|

XsFAD2 gene encodes the enzyme responsible for the high linoleic acid content in oil accumulated in Xanthoceras sorbifolia seeds

Abstract: Results suggested that XsFAD2 is responsible for the high linoleic acid content in X. sorbifolia seed oil. This study provides insight on the regulation mechanism of fatty acid synthesis in X. sorbifolia seeds and a valuable gene for improving the oil quality in oilseed trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The expression level of the FAD2-2 gene rapidly increased from 40 to 54/68 daa in the two lines and then decreased at the mature stage (Fig. 9j), which correlated well with the changes in linoleic acid and the total FA content in developing yellowhorn seeds [8]. Extensive research suggests that FA biosynthesis in higher plants may be an important regulatory step in oil accumulation [51,52].…”
Section: Mirnas and Their Targets Are Related To Yellowhorn Lipid Biosupporting
confidence: 57%
See 1 more Smart Citation
“…The expression level of the FAD2-2 gene rapidly increased from 40 to 54/68 daa in the two lines and then decreased at the mature stage (Fig. 9j), which correlated well with the changes in linoleic acid and the total FA content in developing yellowhorn seeds [8]. Extensive research suggests that FA biosynthesis in higher plants may be an important regulatory step in oil accumulation [51,52].…”
Section: Mirnas and Their Targets Are Related To Yellowhorn Lipid Biosupporting
confidence: 57%
“…Yellowhorn research over the past decade has focused on oil extraction, FA composition, and the use of seed oil as a biodiesel [5][6][7]. Yellowhorn lipid biosynthesis metabolic pathways have been the subject of several studies, which identi ed some key genes associated with oil accumulation [8,9]. For example, two novel diacylglycerol acyltransferase (XsDGAT1 and XsDGAT2) yellowhorn genes were found to control its seed oil content [10].…”
Section: Introductionmentioning
confidence: 99%
“…Yeast has been shown to be an ideal model system for identifying the function of ER-located desaturases, including FAD2 and FAD3 [ 17 , 71 ], but it was not suitable for heterologous expression of plastidial desaturases (e.g. FAD6/7/8) due to their requirements for electron transport chains from the chloroplast [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…To achieve the maximum amount of oil yield, a better understanding of the mechanisms of oil biosynthesis and the specific molecular pathways involved is necessary. Several studies have attempted to examine yellow horn oil biosynthesis metabolic pathways and have identified some genes found to be associated with oil accumulation [ 4 , 5 , 6 ]. One study found that the expression of two novel diacylglycerol acyltransferase genes ( XsDGAT1 and XsDGAT2 ) in transgenic Arabidopsis led to triacylglycerol (TAG) assembly and increased seed oil production [ 4 ]; with the expression patterns of both genes also correlated with oil accumulation in developing yellow horn embryos, presumably via TAG assembly.…”
Section: Introductionmentioning
confidence: 99%